Application of Ionic Liquid [DMIM]DMP Pretreatment in the Hydrolysis of Sugarcane Bagasse for Biofuel Production - Arief Widjaja; Silvya Yusnica Agnesty; Hanny F. Sangian; Setiyo Gunawan (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
Sugarcane bagasse is one of lignocellulose materials that can be converted to biofuel. This work was aimed to develop new pretreatment combination methods to process sugarcane bagasse lignocellulose into biofuel (bio-hydrogen). Pretreatment of sugarcane bagasse using NaOH solution in combination with ionic liquid [DMIM]DMP enhanced the enzymatic hydrolysis significantly. After the pretreat-ment, the content of cellulose and hemicellulose increased by 29.31% compared to the untreated one. Cellulose and hemicelluloses were used as raw materials to produce reducing sugars, that can be con-verted to bio-hydrogen via fermentation. After being subjected to combined pretreatment processes, the crystalline index of sugarcane bagasse decreased significantly compared to solely NaOH pretratment. This indicates a more amorphous structure of the sugarcane bagasse, which makes it is easier to be hy-drolyzed into reducing sugars. The recovery of cellulose + hemicellulose after pretreatment for 20 min and 120 °C was 92%, and the yield obtained was 0.556 g sugars/g (cellulose + hemicellulose) after 12 h and the bio-hydrogen yield was 0.46 mol H2/mol sugars consumed after 48 h fermentation. The use of recycled of ionic liquid showed similar performance compared to the use of fresh ionic liquid. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)